Lexical and grammatical errors in Indonesian-English translated texts: A text analysis on Indonesian EFL students’ translation work - Shiddiq, Salma Mu'min; Oktaviani, Lulud; Herwiana, Sakhi; Suryanovika, Citra (Universitas Muhammadiyah Sidoarjo, 2023)
This current study aimed to find out lexical and grammatical errors in Indonesian to English translation texts made by Indonesian EFL learners in a private senior high school in Lampung. A qualitative case study design was adopted in this research. Documentation and literature review were used as the research instruments. To obtain the data, the researchers used 15 simple sentences and a short text in Indonesian. A total of 25 students participated as the sample in this research. The results suggested that there was a total of 402 errors made by the students and the students made more grammatical errors than lexical errors. Regardless of the discrepancy in students’ CEFR level, the most frequent errors found in students’ translations were omissions (97 items), confusion of sense relations (73 items), misformations (46 items), and distortions (40 items). After identifying the errors, the researchers also attempted to describe the possible sources of errors to fill the gap in previous studies. Based on the analysis, the possible factors influencing the errors were the transfer of phonological system, transfer of lexico-semantic errors, transfer of morphological elements, transfer of grammatical elements, transfer of stylistic and cultural elements in interlingual errors, and communication strategy-based errors and learning strategy-based errors in intralingual errors. HIGHLIGHTS: Both intralingual and interlingual errors played essential roles in influencing students to commit errors when translating texts from Indonesian into English. The students committed more grammatical errors than lexical errors. It is evident that errors are rule-governed and systematic in nature, meaning that the errors committed by the students are not randomly produced but are systematic deviations of patterns in the input of language norms in which the learners have been exposed or have learned.